Pembelajaran berbasis fenomena: Analisis bibliometrik menuju pendidikan siap masa depan - Desy Anisa; Deni Kurniawan; Munir Munir (Curricula: Journal of Curriculum Development, 2026)
The transformation of 21st-century education demands an approach that integrates knowledge, technology, and real-world contexts to foster critical thinking and collaboration, positioning Phenomenon-Based Learning (PhBL) as an innovative model that links authentic experiences with conceptual understanding. This study aims to map and analyze global developments, thematic directions, and digital integration in PhBL research. The method used is a bibliometric approach to 352 Scopus-indexed publications from 1982 to 2024, with performance and science mapping analysis using VOSviewer software. The results show a significant increase in PhBL publications after 2016, peaking in 2024, indicating the growing relevance of this approach in contextual and technology-based learning. Keyword co-occurrence analysis identified five main clusters that describe the paradigm shift in PhBL from human-centered pedagogy to digitally integrated learning. These findings suggest that PhBL has developed into an interdisciplinary framework that integrates pedagogy and technology while addressing Indonesia’s priority education issues, including climate change, health education, and financial literacy. In conclusion, PhBL is a promising learning innovation for realizing meaningful, adaptive, and sustainable learning in facing the challenges of 21st-century education.